Keabsahan kekuatan kontrak dengan menggunakan kontrak elektronik ShopeePayLater - Irawan, Septian Bambang (Maliki Interdisciplinary Journal, 2024)
Internet technology has a very big influence in supporting changes in human lifestyles. With the influence of technology, many innovations have been created to make it easier for humans to make buying and selling transactions. One of the things that makes human work easier is in the buying and selling sector, namely e-commerce (electronic commerce). One of the well-known platforms is Shopee. Where the platform provides lots of online buying and selling features, recently in Shopee there is a feature called Shopee PayLater which provides electronic money loans that make it easy for the community. What is very important to study in this research is the legitimacy of the power of the Shopee PayLater electronic contract by shopee users. The research method used by researchers uses Normative Jurisdiction which uses a conceptual approach to research on the level of legal synchronization. The results of the study show that the validity of the Power of Contract Using the Shopee PayLater Electronic Contract is legal according to the ITE Law in Article 5 paragraph (3).